The Influence Of Altruism And Communication On Employee Performance CV. Jaya Laksana Rattan Majalengka - Anna Suzana (Universitas Sebelas April, Fakultas Ekonomi dan Bisnis, 2023)
This study aims to determine the influence of Altruism and communication On Employee Performance on Cv. Jaya Laksana Rattan Majalengka. The research method used is the quantitative research method. The population in the study was Cv employees. Jaya LaksanaRattan Majalengka. The technique used in sampling uses a saturated sample, for which the population is sampled totaling 68 respondents. The method of data collection used questionnaires, while the method in this study used multiple linear regression analysis. The results of this study showed 11n that Altruism had a significant effect on Employee Performance as viewed from thitung > ttable i.e. 3,980 > 1.996, Communication had a significant effect on Employee Performance as viewed from thitung > ttable which was 7.923 > 1.996 and was simultaneously variable. Altruism and Communication had a positive and significant effect on Employee Performance 101,138 > 3.14. Of the partial results Altruism has a sig value of 0.000 and Altruism has a sig value of 0.000, and the simultaneous result has a sig value < 0.05 or 0.000 < 0.05